A qualitative study to understand the lived experiences of young adults in intercultural romantic relationships, in Durban - Candey, Jennifer (The IIE, 2020)
South Africa is a culturally diverse country, with the number of people getting into intercultural relationships growing each day (Ntuli, 2012). Previous literature has shown a vast amount of knowledge of the experiences of these couples, however there is a lack of focus within the South African context. Without research focusing on the experiences of young adults in intercultural relationships in South Africa, many people are unaware of the experiences of these intercultural couples. The purpose of this research study is therefore to address this problem by conducting a qualitative study on two young couples in an intercultural relationship, in Durban. The couples took part in an online semistructured interview to discuss their experiences of being in an intercultural relationship. The reason for this method was to allow for a certain degree of openness during the interview. Findings show that the females became assimilated into the dominant culture of their partner and that the men, although having a more dominant culture, had become less strict in the practice of their own culture, and that the experience of gender roles within the relationship were found to be equal amongst both couples.
Keywords: Romantic relationships; Young adults; Intercultural relationships; Experiences; Durban